The Effect of Entrepreneurship Education to The Number of Entrepreneur: A Cross-Sectional Study from Indonesia - Yustian, Okky Rizkia; Astuty, Eriana (Jurnal Pendidikan Progresif, 2021)
Entrepreneurship is a science that can be learned, and educational institutions have a role in increasing the number of entrepreneurs. This study aims to find out the relationship between entrepreneurial education and attitude, entrepreneurial self-efficacy, and entrepreneurial intention. The population of this research was university students at Widyatama University, and the sampling method used was purposive sampling. A total of 96 cases were analyzed. The data for the current study were obtained from students who had been and were taking entrepreneurship education. In order to test the validity, reliability, and hypothesis, the SPSS model was used. The results show that attitude has a significant influence on entrepreneurial intention. Another finding shows that entrepreneurial self-efficacy has a significant influence on entrepreneurial intention. Also, the results surprisingly found that entrepreneurship education does not have a significant effect on entrepreneurial intention. After all, this study provides theoretical and managerial contributions to the literature.Keywords: entrepreneurial education, attitude, self efficacy, entrepreneurial intention.DOI: http://dx.doi.org/10.23960/jpp.v11.i3.202115